2017
DOI: 10.3390/coatings8010010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Negative Bias Voltage and Ratio of Nitrogen and Argon on the Structure and Properties of NbN Coatings Deposited by HiPIMS Deposition System

Abstract: The NbN x>1 coatings were deposited on Si wafer and SUS 304 stainless steel substrates by a high power impulse magnetron sputtering (HiPIMS) system at various bias voltages and the ratios of nitrogen and argon (N 2 /Ar). By virtue of electron probe microanalysis (EPMA), X-ray diffraction pattern (XRD), scanning electron microscope (SEM), atomic force microscope (AFM) and nano indentation test, the relationships between deposition parameters and coatings properties were examined in detail. These coatings show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Barshilia et al 13 used DC planar magnetron sputtering to deposit niobium nitride coating on tool steel and obtained a hardness of 17 GPa. Totik 14 12 reported high-power impulse magnetron sputtering to deposit niobium nitride on SUS-304 SS and obtained a hardness of up to 31.3 GPa. This comparison reveals the CCPD technique can obtain effective improvement in hardness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barshilia et al 13 used DC planar magnetron sputtering to deposit niobium nitride coating on tool steel and obtained a hardness of 17 GPa. Totik 14 12 reported high-power impulse magnetron sputtering to deposit niobium nitride on SUS-304 SS and obtained a hardness of up to 31.3 GPa. This comparison reveals the CCPD technique can obtain effective improvement in hardness.…”
Section: Resultsmentioning
confidence: 99%
“…They found improvement in hardness up to 1084, 2040, and 2620 HK 25 for MS, SS, and HSS, respectively. Ding et al 12 examined the role of negative bias voltage on the surface properties of niobium nitride on SUS-304 SS deposited by high-power impulse magnetron sputtering. They observed that increasing the biasing voltage could improve hardness up to 31.3 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that this preferred orientation in TaN films has a positive influence on hardness as shown in Table 1. However, when the nitride ratio in the film exceeds 5%, the preferred orientation shifts from hexagonal-Ta2N structure to cubic-TaN structure, subsequently leading to a decrease in hardness [14].…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that this preferred orientation in TaN films has a positive influence on hardness as shown in Table1. However, when the nitride ratio in the film exceeds 5%, the preferred orientation shifts from hexagonal-Ta2N structure to cubic-TaN structure, subsequently leading to a decrease in hardness[14].Furthermore, the presence of Ta2N (100) in the hexagonal structure significantly influenced the hardness values, particularly in the R1 coating, where the highest hardness value of 28 GPa was achieved. This suggests that the microstructural arrangement of the coatings played a vital role in influencing their hardness property.…”
mentioning
confidence: 99%